1977
DOI: 10.1128/aem.33.2.341-344.1977
|View full text |Cite
|
Sign up to set email alerts
|

Effect of beef broth protein on the thermal inactivation of staphylococcal enterotoxin B1

Abstract: Enterotoxin B produced by Staphylococcus aureus 243 in brain heart infusion broth was concentrated by dialysis against 40% polyethylene glycol (20 M), partially purified on a Sephadex G-100 column and heated at 1100C in thermal death time cans. Various heating menstrua included 0.04 M Veronal buffer (pH 7.4), beef broth, and fractions of beef broth obtained by ultrafiltration or precipitation with ammonium sulfate. The toxin was assayed serologically using the microslide gel double-diffusion method. The time r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Cardinal Fung 1976;Lee et al 1977; Stelma & Bergdoll 1982; Bergdoll 1989) make it impossible to give an accurate figure for the extent of their heat resistance. This is compounded by the effect of the composition of the food substrate on heat inactivation of enterotoxins.…”
mentioning
confidence: 99%
“…Cardinal Fung 1976;Lee et al 1977; Stelma & Bergdoll 1982; Bergdoll 1989) make it impossible to give an accurate figure for the extent of their heat resistance. This is compounded by the effect of the composition of the food substrate on heat inactivation of enterotoxins.…”
mentioning
confidence: 99%
“…The toxin can remain serologically and biologically active after exposure to 121 °C for 19 to 30 min in buffer or beef bouillon (Denny et al, 1971, Humber et al, 1975, Tibana et al, 1987, Anderson, 1996. Denny et al (1971) and Lee et al (1977) demonstrated that using food as the heating medium was shown to increase the thermal stability of staphylococcal enterotoxin Ϸ 2-to 5-fold. They suggested that the food components provided some protective effect possibly through protein-protein interactions (Denny et al, 1971).…”
Section: Foodmentioning
confidence: 99%
“…SEs are resistant to inactivation by gastrointestinal proteases such as pepsin. Heat stability is one of the most important physical and chemical properties of SEs in terms of food safety (Denny et al 1971;Humber et al 1975;Lee et al 1977;Hoover et al 1983).…”
Section: Introductionmentioning
confidence: 99%